Statistical Indicators of Groundwater Geochemical Characteristics in a Quaternary Aquifer from the Mala Mlaka Well Field Catchment Area (Zagreb, Croatia) - Zoran Nakić (Geologia Croatica, 2005)
High concentrations of sodium, potassium, nitrates and sulphates in the groundwater in the Mala Mlaka well field catchment area confirm the impact of agricultural activities on water chemistry. Analysis of time trends has shown that a decrease in inorganic components (nitrates and sulphates), which are sensitive to changes in oxidation/ reduction conditions in an aquifer, are caused by infiltration of oxygen- rich water rich in organic matter into the aquifers. Oxygen content reduction due to oxidation of the organic matter causes oxygen deprivation in the groundwater and consequently a reduction in nitrate and sulphate levels. An increase in chloride levels in the groundwater during 1994–2000 is a consequence of human activities in the catchment area. Multivariate statistical analyses, i.e. factor analysis, cluster analysis and multidimensional scaling (MDS) analysis have shown that the registered pollution sources in the catchment area, particularly illegal dump sites, cause degradation of the groundwater quality in some sites. This impact is detected over a distance of several hundred metres downstream from the registered pollution sources.